Associations Between Abstract Concepts: Investigating the Relationship Between Deictic Time and Valence - Kaup, Barbara; Scherer, Nina; Ulrich, Rolf (Frontiers in Psychology, 2021)
The present study examines whether deictic time and valence are mentally associated, with a link between future and positive valence and a link between past and negative valence. We employed a novel paradigm, the two-choice-sentence-completion paradigm, to address this issue. Participants were presented with an initial sentence fragment that referred to an event that was either located in time (future or past) or of different valence (positive or negative). Participants chose between two completion phrases. When the given dimension in the initial fragment was time, the two completion phrase alternatives differed in valence (positive vs. negative). However, when the given dimension in the initial fragment was valence, the two completion phrase alternatives differed in time (future vs. past). As expected, participants chose completion phrases consistent with the proposed association between time and valence. Additional analyses involving individual differences concerning optimism/pessimism revealed that this association is particularly pronounced for people with an optimistic attitude.